Place-Based Education: A Critical Review - Gnyawali, Bishal; Sapkota, Kanhaiya; Paudel, Devi (The Geographic Base, 2024)
This article critically investigates ways in which place-based education is understood and enacted in local school and community contexts, showing intersections between place, power and pedagogy and their influence on one's capabilities to sustain or resist normative educational narratives and to suggest the transformative possibility of critical education engaged with place. Theoretical foundations for place-based education are anchored in constructivist, experiential, ecological and sociocultural models of learning, and emphasizes in such a way that students learn in those local contexts that ground the academic content in objectives of student engagement, problem solving and critical thinking across disciplines. The outcomes of place-based education are numerous and include interdisciplinary learning, environmental stewardship, and sustainability of communities. The challenges to implementation in a more mainstream way of teaching and learning include issues with curriculum, teacher preparation and professional development, and systems of educational instruction. Through qualitative analysis of literature published between 1979 and 2024 we found not only better practices for place-based education, including preparation and professional learning, curriculum, and authentic partnerships with community. The article offers recommendations for sustainability of PBE in the future through policy and support, and through longitudinal studies, since much of the research is not long term and acknowledges context.